Africa’s global trade patterns - Traoré, Fousseini; Sakyi, Daniel (International Food Policy Research Institute, 2018)
Chapter 2, by Fousseini Traore and Daniel Sakyi, examines trends and patterns in Africa’s global agricultural trade during the 1998–2013 period. The study assesses trends in overall trade volumes and values, and in the trade of key agricultural commodities. The chapter then analyzes the direction of agricultural exports and imports, changes in market shares, and changes in the composition of Africa’s exports and imports, to provide a comprehensive overview of Africa’s agricultural trade with the rest of the world.